2022
DOI: 10.1177/0306624x221139073
|View full text |Cite
|
Sign up to set email alerts
|

Which Clinical and Demographic Factors are Related to Incarceration in Male Patients With Antisocial Personality Disorder?

Abstract: Antisocial Personality Disorder (APD) is a condition largely represented in detention centers where can reach a prevalence of 60% in male prisoners. The objective of this study is to identify the clinical and demographic factors that differentiate subjects with APD and hosted in penitentiary with respect to those are treated in outpatient psychiatric clinics. We recruited 65 male patients affected by APD, whose 26 were followed up in community mental health services and 39 were serving their sentence in a dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, prisons contain some of the most vulnerable and disadvantaged individuals in society. Indeed, it is consistently reported that individuals experiencing mental illness are overrepresented in prison populations than those of similar ages living in community (Fazel and Seewald, 2012; Esposito et al ., 2022), particularly in case of co-occurring serious mental illnesses and substance use disorders (dual diagnosis) (Fazel et al ., 2016; Baranyi et al ., 2022). Of note, people who are incarcerated are a highly fragile population as demonstrated by high rates of self-harm, suicide, victimization, violence, poverty, unemployment, family breakdown, homelessness, physical health problems as well as of reoffending and eventual reincarceration (Wallace and Wang, 2020; Capuzzi et al ., 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…However, prisons contain some of the most vulnerable and disadvantaged individuals in society. Indeed, it is consistently reported that individuals experiencing mental illness are overrepresented in prison populations than those of similar ages living in community (Fazel and Seewald, 2012; Esposito et al ., 2022), particularly in case of co-occurring serious mental illnesses and substance use disorders (dual diagnosis) (Fazel et al ., 2016; Baranyi et al ., 2022). Of note, people who are incarcerated are a highly fragile population as demonstrated by high rates of self-harm, suicide, victimization, violence, poverty, unemployment, family breakdown, homelessness, physical health problems as well as of reoffending and eventual reincarceration (Wallace and Wang, 2020; Capuzzi et al ., 2021a).…”
Section: Introductionmentioning
confidence: 99%